Modeling, optimization, and control of microbial electrolysis cells in a fed-batch reactor for production of renewable biohydrogen gas - Yahya, A.M.; Hussain, Mohd Azlan; Wahab, Ahmad Khairi Abdul (John Wiley & Sons, 2015)
An integrated modeling, optimization, and control approach for the design of a microbial electrolysis cell (MEC) was studied in this paper. Initially, this study describes the improvement of the mathematical MEC model for hydrogen production from wastewater in a fed-batch reactor. The model, which was modified from an already existing model, is based on material balance with the integration of bioelectrochemical reactions describing the steady-state behavior of biomass growth, consumption of substrates, hydrogen production, and the effect of applied voltage on the performance of the MEC fed-batch reactor. Another goal of this work is to implement a suitable control strategy to optimize the production of biohydrogen gas by selecting the optimal current and applied voltage to the MEC. Various simulation tests involving multiple set-point changes, disturbance rejection, and noise effects were performed to evaluate the performance where the proposed proportional-integral-derivative control system was tuned with an adaptive gain technique and compared with the Ziegler-Nichols method. The simulation results show that optimal tuning can provide better control effect on the MEC system, where optimal H-2 gas production for the system was achieved. Copyright (c) 2014 John Wiley & Sons, Ltd.